2016
DOI: 10.1016/j.neurobiolaging.2016.03.029
|View full text |Cite
|
Sign up to set email alerts
|

The role of the melanoma gene MC1R in Parkinson disease and REM sleep behavior disorder

Abstract: The MC1R gene, suggested to be involved in Parkinson disease (PD) and melanoma, was sequenced in PD patients (n=539) and controls (n=265) from New-York, and PD patients (n=551), rapid eye movement sleep behavior disorder (RBD) patients (n=351) and controls (n=956) of European ancestry. Sixty-eight MC1R variants were identified, including 7 common variants with frequency>0.01. None of the common variants was associated with PD or RBD in the different regression models. In a meta-analysis with fixed-effect model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 42 publications
1
16
1
Order By: Relevance
“…A). When we further examined two MC1R red hair color alleles, we found that p.R151C variant was associated with marginally increased risk of PD (pooled OR = 1.101; 95% CI: 1.002, 1.210; P = 0.046; PD case number = 8454] (Fig. B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A). When we further examined two MC1R red hair color alleles, we found that p.R151C variant was associated with marginally increased risk of PD (pooled OR = 1.101; 95% CI: 1.002, 1.210; P = 0.046; PD case number = 8454] (Fig. B).…”
Section: Resultsmentioning
confidence: 99%
“…We identified six publications based on eight study cohorts in total from 2009 to 2016, all with study focus on hair color or MC1R p.R151C or p.R160W polymorphisms (Table ) . PD cases were of US, French/French‐Canadian, UK, German, Greek, Dutch, and Spanish origins, overall representing white populations . PD diagnosis was generally ascertained by a neurologist or clinician according to the United Kingdom Parkinson's Disease Society Brain Bank Criteria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…15 The association was substantiated by another study linking PD with an alternative red hair MC1R variant in an independent cohort. 16 Although other studies [17][18][19][20] did not replicate a significant MC1R-PD association, which may be attributable to technical or population differences across studies, 21 MC1R has nevertheless emerged as having a potential role at the interface of melanoma and PD.…”
mentioning
confidence: 97%